Relationship between the acceptance of multiframe visualization assisted teaching approach VATA interactive with student interest and motivation in blended learning among music students in Universiti Pendidikan Sultan Idris - Abdul Ghafar, Mohd Haizal; Ghazali, Norliza (Macrothink Institute, 2022)
Students in the 21st century have been through and dealing with various teaching technologies to acquire knowledge more quickly and accurately. The learning methods of music education especially in the subject of music can be taught using various learning platforms. Therefore, it is necessary for a student to diversify the learning approaches that are used in the classroom. Blended learning is a method that combines classroom interaction with the use of technology in the teaching and learning process. To facilitate blended learning in learning in music courses, this multiframe VATA interactive is one of the educational technology mediums to assist students in further improving the learning process effectiveness. The objective of this study is to determine whether there is a relationship between the acceptance of multiframe VATA interactive with student motivation and student interest. This research will be conducted at the Faculty of Music and Performing Arts, Universiti Pendidikan Sultan Idris, Tanjong Malim, Perak. The sample was selected based on a simple random sampling method whereby 237 samples will be collected from undergraduate random sampling method whereby 237 samples will be collected from undergraduate bachelor music students. This study will utilize a correlational research design. The questionnaire with 46 items was adapted based on the Unified Theory of Acceptance and Use of Technology (UTAUT), Interest Driven Theory (IDC) and ARCS Motivation Theory. The study conceptualized acceptance of VATA in performance expectancy, effort expectancy, social influence and facilitating conditions dimensions while conceiving student interest as having triggering interest, immersing interest and extending interest dimensions and student motivation with attention, relevance, confidence and satisfaction dimensions. Descriptive and inferential statistics will be carried out for data analysis by using Statistical Package for Social Sciences (SPSS) version 27. The findings will be provided further insights into what works in an open online environment as well as to fulfill learners’ needs and preferences.